Implementasi Pembelajaran Berbasis E-Modul Pada Program Paket C di Homeschooling Pena Surabaya - Salsabila, Rodliyyah Zam; Nugroho, Rivo (J+PLUS UNESA, 2026)
This research aims to analyze the implementation of e-module-based learning in the Paket C Program at Homeschooling Pena Surabaya within the context of non-formal education. This research employed a qualitative approach with a case study design and used thematic analysis techniques. The results showed that the HSPENA application was utilized as a learning platform containing e-modules, instructional videos, evaluations, and student learning reports. The use of e-modules helped students access learning materials flexibly and supported independent learning. In addition, the integration of instructional videos and equivalency modules from SIBI (Sistem Informasi Perbukuan Indonesia) expanded learning resources in non-formal education. These findings are in line with the andragogy theory proposed by Malcolm Knowles, which emphasizes independent and flexible learning. Therefore, e-modules function not only as learning media but also as support for learner-centered and independent learning processes.